Coordinating the processes of resource enrichment and capability deployment: Lessons from IT implementation at a medium-sized accounting firm. Issue 4 (30th September 2014) - Pan, Gary; Teoh, Sayyen; Sun Seow, Poh
Abstract : Purpose: – The purpose of this paper has been to address the research question of how are the processes of resource enrichment and capability deployment coordinated during information technology (IT) implementation at a small- and medium-sized accounting firm (SMAF)? Increasingly, organizations need to respond to a wide range of IT-based opportunities and pressures. The situation is no different in an accounting firm. Many accounting practitioners have advocated investment in IT to improve accounting firms' productivity. To date, there are many instances of how IT has radically transformed the nature of accounting practice. Nevertheless, little is known about how IT capability is developed in SMAFs. In particular, the resource enrichment process during IT capability development has been understudied. Design/methodology/approach: – The strategy of this paper was to undertake qualitative case research of an ERP systems upgrading project at SMAF. The case study approach is particularly appropriate for this exploratory study because it allows the capture of organizational dynamics of the phenomenon better (Newman and Sabherwal, 1996; Yin, 2003). Its strength also lies in its ability to explain the phenomenon based on the interpretation of data (Klein and Myers, 1999). Next, the paper will explain the case study approach. It approached fieldwork at SMAF, with a premise that resource enrichment and capability development exist and are identifiable using an existing theoretical lens. Accordingly, this study draws on Sirmon et al. (2007) 's concept of resource enrichment process and objectively studied the IT capability development process through the resource enrichment lens. At the same time, it was recognized that resource enrichment and capability development may have their own unique characteristics, unrelated to any theoretical models offered in the organizational literature. Findings: – The purpose of this paper has been to address the research question of how resource enrichment process may occur during IT capability development process of an SMAF. This study used a resource-based view of firms as its analytical lens. The study has drawn on SMAF's sage ACCPAC ERP solution (ACCPAC) system upgrading experience by interviewing relevant project stakeholders and reviewing secondary data extensively. Our analysis identified two actions that were instrumental in enriching resources in the IT capability development process: collective leadership and managing change. Three attributes that supported the resource-enrichment process include effective governance structure, extensive IT knowledge and business experience, and stakeholder commitment. In addition, two coordinating mechanisms were put in place to enable an organization to transform existing resource and capability: informational and IT structure. Originality/value: – From research point of view, this paper makes several theoretical contributions. First, this study has contributed to the accounting information systems literature by examining the transformation processes of resource and capability enrichment during IT implementation of a context that is little known. It helps to address the call for more research into IT use and the impact of such tools by SMAFs by Omoteso and Sangster (2011). Second, this study extends the understanding of the IT capability development process by demonstrating how an organization developed IT capability. Through this case, how fundamental resources can be leveraged through specific actions and strategies undertaken have been uncovered. The empirical evidence gathered in the case of SMAF provides useful insights into how resources and capabilities may be enabled. Third, the coordination of the resource and capability transformation contributes to theory development as the coordination mechanisms derived from this analysis offer an insights into how a set of enriched resources and capabilities are synchronized during IT implementation.